2021
DOI: 10.21873/anticanres.15283
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy in Patients With Pancreatic Adenocarcinoma. Is It Still Appealing in Clinical Trials? A Meta-analysis and Review of the Literature

Abstract: Aim. Pancreatic adenocarcinoma is a lifethreatening disease with a rising frequency and the fourth leading cause of cancer death. This review aimed to assess the impact of postoperative radiotherapy through a meta-analysis of prospective randomized studies. Materials and Methods: Six studies met the inclusion criteria and were analyzed to calculate the cumulative risk of death (hazard ratio) in patients affected by pancreatic cancer treated with or without radiotherapy. Higgins' index was used to determine het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Primary screening of high-risk factors of PAAD has no standard. By contrast, CT, MRI, positron emission tomography/computed tomography is utilized to diagnose PAAD [2]. However, most patients with PPAD are already in advanced stages, and they have missed the opportunity for surgical treatment after being diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Primary screening of high-risk factors of PAAD has no standard. By contrast, CT, MRI, positron emission tomography/computed tomography is utilized to diagnose PAAD [2]. However, most patients with PPAD are already in advanced stages, and they have missed the opportunity for surgical treatment after being diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency of specific early symptoms of PAAD and the fact that the majority of patients are experiencing advanced progression or organ metastases contribute to PAAD being a high-mortality cancer (2). Frustratingly, radiotherapy, as well as chemotherapy, were not effective options in the treatment of PAAD, and surgical resection was currently the best option for most patients, but the prognosis was graded poorly, with an overall 5-year survival (OS) rate of less than 10% (3)(4)(5). Several studies have shown that prognosis in a variety of cancers, including PAAD, can be predicted using carbohydrate antigen and carcinoembryonic antigen (CEA) (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…For pancreatic ductal adenocarcinomas (PDAC) conventionally fractionated radiotherapy with concurrent chemotherapy using elective nodal irradiation either in the neoadjuvant or adjuvant setting was largely unsuccessful in terms of improving survival 21 , 22 . Stereotactic radiotherapy is evolving for locally advanced PDAC, but with small margins a precise determination of tumor spread is mandatory 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%